1994
DOI: 10.1046/j.1537-2995.1994.34694295069.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivities of viruses in red cell suspensions to methylene blue photosensitization

Abstract: MB-based protocols would require the use of high-efficiency (> 6log10) white cell-reduction filters or additional inactivation steps to deplete or inactivate intracellular virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…To date, this is the most extensive report documenting inactivation of a broad spectrum of infectious viruses and bacteria in full-sized platelet concentrates. Other potential decontamination systems have not demonstrated this degree of activity [28][29][30]. The PCT process described in this study is antiviral and antibacterial.…”
Section: Lack Of Neoantigen Formation On Pct Plateletsmentioning
confidence: 74%
“…To date, this is the most extensive report documenting inactivation of a broad spectrum of infectious viruses and bacteria in full-sized platelet concentrates. Other potential decontamination systems have not demonstrated this degree of activity [28][29][30]. The PCT process described in this study is antiviral and antibacterial.…”
Section: Lack Of Neoantigen Formation On Pct Plateletsmentioning
confidence: 74%
“…Therefore, the simple addition of MBP to cellular components would not eliminate the risk of virus transmission. Additional inactivation steps would be required to deplete intracellular virus 28 . Studies of photo‐dynamic treatment of PCs have shown that direct exposure of platelets to MB photoinactivation cannot inactivate virus without damaging platelets 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the technique also does not inactivate all nonenveloped viruses, the technique can be applied on each unit individually; thus the risk of transmission of these viruses is not increased by the MB process. However, by itself, MB treatment provides inadequate inactivation of intracellular viruses [10]. Thus, for the process to provide substantial assurance of inactivation, an additional step, such as disruption of leukocytes via a freeze/thaw cycle, is necessary.…”
Section: Introductionmentioning
confidence: 99%